Evaluation of crop and irrigation water requirements for some selected crops in Apulia region -Southern Italy - Alobid, Mohannad; Szűcs, István (Applied Studies in Agribusiness and Commerce, 2019)
Nowadays, nearly 90% of global water consumption is caused by irrigation activities, and more than 40% of the crops are produced under irrigated conditions. This study is an endeavour to estimate the irrigation water requirement (IWR) and crop water requirement (CWR) for some selected crops (Pepper, Eggplant, Potato, Soybean, Maize, Wheat Melon, Lettuce, Sunflower, Broadbean, Citrus, Cherry, Olive tree, Sugarbeet, Artichoke, Wine Grapes, Carrot...etc.) in Sothern Italy. The selected districts (Sant’ Arcangelo) have been taken as a case study area. Demanded meteorologically (rainfall, temperature, humidity, wind speed, sunshine hours) and crop data (crop coefficient and crop calendar) have been collected for 30 years period from 1981 to 2011. FAO CROPWATv8.0 software has been applied for requisite calculation of CWR and IWR along with the developing of cropping patterns. The FAO Penman-Monteith equation is used for estimating the reference evapotranspiration (ET0) by using meteorological data in the framework of CROPWAT model as it regarded as a good evaluator for a wide variety of climatic conditions. The analysis indicates that FAO Penman-Monteith suits very well for the study area and can be successfully used for the estimation of reference evapotranspiration. The important results in this study indicate that the IWR is very low from November to April (wintertime) due to higher rainfall intensity in these months and from month May to October a considerable amount of water is required for irrigation.JEL Classification: Q25, Q24,Q10